Breastfeeding Behavior in Brazilian Children with Congenital Zika Syndrome - Alidianne Fábia Cabral Cavalcanti; Yêska Paola Costa Aguiar; Adriana Suely De Oliveira Melo; Alessandro Leite Cavalcanti; Sergio D'Ávila (Hindawi Limited, 2020)
Congenital Zika Syndrome (CZS) is a condition that has emerged only recently, bringing together multiple changes, including significant changes in the stomatognathic system, which may compromise sucking behavior and consequently the breastfeeding practice. The aim of this study was to investigate the breastfeeding behaviors in children with CZS. A longitudinal study was carried out in two reference centers in Northeastern Brazil. The nonprobabilistic sample consisted of 79 children diagnosed with physical, neurological, and behavioral alterations compatible with CZS. Information regarding the child, nutritive, and nonnutritive sucking behavior and changes related to the sucking reflex was collected. Data were presented through descriptive and inferential statistics. In the bivariate analyses, the chi-squared test was used and 5% significance level was adopted. The majority of children had severe microcephaly (59.7%). Breastfeeding was performed at birth in most of CZS children (89.9%) but only 36.6% of them presented exclusive breastfeeding in the six months of life. Bottle feeding and pacifier were used in 89.9% and 55.7%, respectively. Sucking and swallowing difficulties and occurrence of gastroesophageal reflux were observed in 27.8%, 48.0%, and 29.2% of children, respectively. Early weaning was associated with bottle feeding (p=0.005) and pacifier sucking (p=0.003). Although breastfeeding practice at birth constitutes a behavior adopted by most of mothers, adherence to this exclusive habit until the first six months of life was low since the children presenting a large number of comorbidities with direct interference in the suction reflex, sucking, and swallowing difficulty.